Pengaruh Pemasaran terhadap Minat Menggunakan Produk Bank Syariah pada Generasi Z - Zuhrinal M. Nawawi; Popi Dea Ananda (Jurnal Penelitian Ilmu Ekonomi dan Keuangan Syariah, 2025)
This research uses a qualitative method to examine the influence of marketing strategies on the interest in using Islamic banking products among Generation Z. This generation has unique characteristics in accessing information and making financial decisions, including the selection of banking services. Marketing strategies employed by Islamic banks—such as digital promotion, emotional appeal, and Islamic values—play a crucial role in attracting the attention of this generation. The study aims to understand how the elements of marketing—product, price, place, and promotion—affect Generation Z’s perception and preference toward Islamic banking products. Data were collected through in-depth interviews with informants from among university students and Islamic banking practitioners. The analysis results show that the use of social media, delivery of religious values, and ease of access are dominant factors in increasing interest. These findings contribute to the development of relevant and effective marketing strategies for Islamic banks to expand their market among digitally literate and spiritually aware young generations.